From gnostics to monastics : studies in coptic and early christianity in honor of Bentley Layton - Layton, Bentley.; Brakke, David.; Davis, Stephen J.; Emmel, Stephen. (Orientalia Lovaniensia analecta, 2017)
This collection of studies is offered in honor of Bentley Layton by twenty-three of his colleagues and former students. Prof. Layton taught the history of ancient Christianity and also the Coptic language at Yale University for forty years beginning in 1976. At that time he was already recognized internationally as a leading figure in the publication and study of the Coptic Gnostic texts from the Nag Hammadi Codices and in Coptic linguistic and manuscript studies, two areas of research that are represented in this volume by sections on Gnostic, Valentinian, and Manichaean literature, and on Coptic language and texts. A section on Egyptian monasticism pays tribute to Prof. Layton's fundamental contributions to the study of the late antique monastic leader and Coptic author Shenoute. A final section looks north across the Mediterranean Sea to early Chistianity in the Wider Late Roman World.